A Weak Galerkin Finite Element Method for the Linear Elasticity Problem in Mixed Form (Journal of Computational Mathematics, 2018)
In this paper, we use the weak Galerkin (WG) finite element method to solve the mixedform linear elasticity problem. In the mixed form, we get the discrete of proximation of thestress tensor and the displacement field. For the WG methods, we define the weak functionand the weak differential operator in an optimal polynomial approximation spaces. Theoptimal error estimates are given and numerical results are presented to demonstrate theefficiency and the accuracy of the weak Galerkin finite element method.